2019
DOI: 10.1111/pops.12589
|View full text |Cite
|
Sign up to set email alerts
|

The Political Consequences of Combat: Post‐Traumatic Stress and Political Alienation Among Vietnam Veterans

Abstract: On average, veterans are more civically and politically engaged than civilians. Previous research on the effects of military service, however, did not account for differences in veterans’ combat experiences. Using survey data from a representative sample of Vietnam veterans, this study presents evidence that veterans who were exposed to severe combat trauma and veterans who exhibited attitudes and fears associated with post‐traumatic stress had significantly lower levels of political efficacy and trust. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Equally troubling is the reluctance of some clinicians to delve too deeply into the experiences of returning veterans ( van der Kolk, 2014 ; Carless and Douglas, 2016 , p. 375). Therefore, veterans with post-traumatic stress often experience difficulties in trusting others—be they clinicians, physicians, therapists, or government officials—and in maintaining emotional intimacy with loved ones, in large part because they feel misunderstood and isolated ( Shay, 1994 ; Usry, 2019 ). Therefore, truly listening to and creating trust among veterans is of the outmost importance.…”
Section: Descriptions Of the Contexts And Challenges Due To Military Servicementioning
confidence: 99%
“…Equally troubling is the reluctance of some clinicians to delve too deeply into the experiences of returning veterans ( van der Kolk, 2014 ; Carless and Douglas, 2016 , p. 375). Therefore, veterans with post-traumatic stress often experience difficulties in trusting others—be they clinicians, physicians, therapists, or government officials—and in maintaining emotional intimacy with loved ones, in large part because they feel misunderstood and isolated ( Shay, 1994 ; Usry, 2019 ). Therefore, truly listening to and creating trust among veterans is of the outmost importance.…”
Section: Descriptions Of the Contexts And Challenges Due To Military Servicementioning
confidence: 99%
“…In turn, these factors reflect on the individual perception and sense-making of military reality ( Molendijk et al, 2022 ). Other research on US conscripts in Vietnam has indicated that exposure to violence and the development of PTSD impacts veterans’ political involvement through lower political efficacy and trust due to feelings of betrayal, isolation, and helplessness, regardless of the social support available ( Usry, 2019 ). The Vietnam veterans’ experience was typified by a disconnect between the veteran and the perception of the military in the politics of the populace and, eventually, the government on their return from duty.…”
Section: Introductionmentioning
confidence: 99%
“…Both processes have increased the prominence of security and the military in driving Israeli politics ( Levi and Agmon, 2021 ). Therefore, it could be that many Israeli veterans – who, like many veterans around the world, are more likely to be politically engaged, more likely to vote, and more likely to be on the right of politics ( Usry, 2019 ) – will maintain their views of the importance of the military in society for continued security purposes. This will be reflected in their political statements and, in Israel, will mirror more comprehensive societal views and may positively impact their adaptation after military service.…”
Section: Introductionmentioning
confidence: 99%